Impact of Atypical Hyperplasia at Surgical Margins on breast cancer outcomes in patients treated with neoadjuvant chemotherapy - Su, An; Zhang, Jing; Liu, Jieqiong; Yang, Yaping; He, Zhou; Bao, Haoshi; Deng, Heran; Wu, Jiannan (Frontiers in Oncology, 2023)
Background Women with atypical hyperplasia (AH) is associated with a higher risk of future breast cancer. However, whether AH found at margins in patients with breast-conserving surgery (BCS) after neoadjuvant chemotherapy (NAC) needs re-excision is not well-defined. The aim of the present study was to evaluate the impact of atypical hyperplasia at the surgical margins on the local recurrence and survival outcomes in breast cancer patients treated with NAC and BCS. Methods A retrospective analysis comparing patients who treated with NAC and BCS with AH at the margins to those without AH was performed. Results 598 patients were included in this study. The 5-year rates of ipsilateral breast tumor recurrence (IBTR) were 4.6% and 6.2% in patients with and without AH, respectively. No significant differences were observed among the two groups in terms of IBTR, DMFS, or OS. HER-2 overexpressing breast cancer patients with severe atypical hyperplasia at margins have a significantly higher risk of IBTR compared to those without severe atypical hyperplasia. Conclusion Our study suggests that the presence of AH at the surgical margins of breast conserving surgery (BCS) in patients who received neoadjuvant chemotherapy (NAC) does not appear to increase the risk of ipsilateral breast cancer. Therefore, there is no need for surgeons to routinely perform additional re-excision of AH found at the margins of BCS in these patients. However, selective re-excision should be considered in certain cases, particularly in patients with HER-2 overexpression.